Development of Augmented Reality Based Crawl Swimming Learning Module For Students of The UNU Blitar Sport Education Study Program - Peni Nohantiya; Fatra Nonggala Putra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2020)
Swimming is a compulsory subject in the UNU Blitar Sports Education Study Program curriculum. Has a fairly high Semester Credit Unit (SKS) weight of 4 credits. The crawl style swimming is the basis of all styles so that it needs to be studied more deeply according to the era of the industrial revolution 4.0, namely with a touch of Augmented Reality (AR) technology. This study aims to develop a learning module for swimming crawl style which is integrated with Augmented Reality (AR). The method used by researchers is the Research and Development developed by Dick and Carey which consists of 10 steps. However, due to existing limitations, the researcher only carried out 9 steps. The module was validated by 3 experts, namely: media expert, learning expert, and swimming expert. The input from experts is used to complement the product. Subsequently carried out small group trials totaling 6 students while 30 students as large group trial subjects. The results obtained are: the criteria for product clarity obtained by a percentage of 91.17647% are very valid, the strategic criteria obtained by a percentage of 83.33% are quite valid, the evaluation criteria obtained by a presentation of 75% are quite valid. All criteria have met product eligibility. Product development of the module is declared valid enough and fit for use as a medium to maximize the learning process.